EIGHTEENTH BRUMAIRE IN THE UNITED STATES, GERMANY,AND FRANCE, 1852-1933 - Stark, Sam. Link ([S.l.])
1 online resource
Keywords: The Eighteenth Brumaire in the United States, Germany, and France, 1852-1933 is the first extended political history of Karl Marx's seminal text.Written largely in an engaging narrative form that centers political actors engaging with the text, the book uses published and archival sources to reconstruct the contexts of editions in three languages over eight decades. Stark begins with a new interpretation of the origins of the Brumaire in a context of arguments among revolutionaries in exile, then surveys the main features of its republication in Germany and initial reception (1860-870), its uptake by socialists in Germany and France (1872-892), its status in Germany, France, and the United States before the First World War, and its fate in the Weimar Republic (1918-933).Convincingly proving that the history of the Eighteenth Brumaire should matter for our understanding of Marx today, this book will be fresh for specialists but accessible for diligent students and others without any special background.